Effect of Diabetes mellitus Type 2 on Pituitary Gland Hormones (FSH, LH) in Men and Women in Iraq - Hussein, Zyad; Al-Qaisi, Jawad (Al-Nahrain Journal of Science, 2012)
The objective of this cross sectional study was to assess the effect of diabetes mellitus (DM) type2 on pituitary gland hormones (FSH and LH) in both men and women. This study comprised a total of (108) subjects out of which (50) were normal and the rest (58) were diabetic since more than 5 years. Fasting blood sugar, HbA1c, LH and FSH were measured in blood samples. The results obtained indicated a significant reduction of serum LH, FSH in women with DM comparison to non diabetics and a significant reduction of serum LH and FSH in men with DM comparison to non diabetics. Conclusion: the data from this study show reduction in serum FSH and LH of diabetic patients of both sex compared to healthy individuals.